TRANSPORTASI AIR DALAM PERDAGANGAN PADA MASA JAWA KUNO DI JAWA TIMUR - Hedwi Prihatmoko (Balai Arkeologi Bali, 2014)
Indication of water transportation usage in inscriptions has been available in the early of 10th Century in Central Java, but epigraphic data shows that the mentions of it are more frequent in inscriptions from East Java. Water transportation usage was connected with trade because various type of water transportations are commonly found in the list of traders. This study aims to understand the usage and roles of water transportation in trade to reconstruct the utilization of waterways during Ancient Java period in East Java. Data were collected from transcriptions of published inscription. Data analysis was done through language aspect analysis and the comparison with other languages, ancient manuscripts and foreign literatures. This study shows that during Ancient Java period, various types of water transportations used in river and sea had important roles in internal and external trade. Their roles were also supported by officer or operator and facilities related to them. Indikasi penggunaan transportasi air pada prasasti telah ada sejak awal abad X Masehi di Jawa Tengah, tetapi data epigrafi menunjukkan bahwa penyebutannya lebih banyak di Jawa Timur. Penggunaan transportasi air tersebut berkaitan dengan perdagangan karena kebanyakan disebutkan dalam kelompok pedagang. Kajian ini bertujuan mengetahui penggunaan dan peran transportasi air dalam perdagangan untuk merekonstruksi pemanfaatan jalur perhubungan air pada masa Jawa Kuno di Jawa Timur. Pengumpulan data dilakukan melalui penelusuran transkripsi prasasti yang diterbitkan. Analisis dilakukan berdasarkan aspek bahasa dan perbandingan dengan bahasa lain, naskah kuno, serta berita asing. Kajian ini menunjukkan bahwa pada masa Jawa Kuno, jenis-jenis transportasi air bagi wilayah sungai dan laut berperan penting dalam perdagangan internal dan eksternal yang ditunjang juga oleh petugas atau pengelola dan fasilitas pendukung yang berkaitan dengan sarana transportasi air.